The extraction of Cr (VI) from aqueous solution with a mixture of TEA and TOA as synergic extractant by using different diluents - Saw P.K.; Prajapati A.K.; Mondal M.K. (My University, 2025)
Synergistic extraction of Cr (VI) from aqueous solution was performed by using a mixture of triethylamine (TEA) and trioctylamine (TOA) in different diluents. The maximum extraction of Cr (VI) was obtained as 98.95% with toluene as a diluent at optimum conditions. The various extractants were experimented to find out the suitable synergic mixture and their corresponding percentage extraction was reported. The influence of different analytical parameters such as pH, temperature, equilibrium time, initial concentration of Cr (VI), organic to aqueous (O/A) ratio was performed. Thermodynamic studies showed the process to be exothermic, and Gibb's free energy change and entropy change collectively indicated the extraction process to be reversible and spontaneous. The organic phase after the extraction process was characterized using FTIR spectroscopy which confirms a new ion pair formation. The organic phase containing the metal extractant can be regenerated using different reducing agents such as ascorbic acid, NaOH, etc. The effect of diverse ion of varying concentration was studied to find out their interference in the extraction process. The method was applied to the extraction of Cr (VI) from synthetic effluent as well as a real untreated tannery wastewater sample and the results were found to be satisfactory. © 2018 Elsevier B.V.